Global Health: Shared Obligations and Mutual Respect - Lawrence O. Gostin (Ubiquity Press, 2019)
The commentary provides support for the article "Not Above the Law: A Legal and Ethical Analysis of Short-Term Experiences in Global Health" by Rowthorn et al. Gostin supports the paper's assertion that anyone participating in health care activities in any setting (both at home and abroad) must abide by applicable laws and regulations. Engaging in such work without doing so reflects an outdated - and destructive - model of aid that presupposes and imposes an inherently unequal relationship that thwarts the goals and values of global health. He concludes that there can be no double standards and no ethical or legal values that apply in rich nations but not in countries that host health care volunteers.